Effect of Labisia pumila (Kacip Fatimah) on stress induced changes in leukocyte count and organ weight of albino rats - Alim, Fadillah (2004)
The extract of Labisia Pumila was screened for its effects on stress induced changes in leukocyte count and organ weight of albino rats (Wistar strain). The total leukocyte count in rats was significantly reduced after exposure to noise stress. The neutrophil percentage was increased significantly but, there was significant decrease in the percentage of eosinophils and lymphocytes after exposure to noise stress. Noise stress caused signi~cant increase in the weight of adrenal glands whereas weight of thymus and spleen were decreased significantly. Pretreatment of rats with the extract of Labisia Pumila daily ( 1 00 mg/ kg body weight) for one week, prevented the changes in total leukocyte count, differential leukocyte count and organ weight induced by acute noise stress. The results of this study indicate that the plant, Labisia pumila has an antistressor affect against noise.